Periodontitis and arterial stiffness: a systematic review and meta-analysis - Schmitt, Audrey; Carra, Maria Clotilde; Boutouyrie, Pierre; Bouchard, Philippe (Journal of clinical periodontology, 2015)
Introduction and Aims Patients with periodontitis have a higher risk of cardiovascular diseases, although a causal relationship between these conditions remains unclear. Arterial stiffness is considered a marker of arteriosclerosis and a risk factor for cardiovascular diseases. A systematic review of the literature on clinical studies using pulse wave velocity (PWV) to assess arterial stiffness in patients with periodontitis was carried out to answer the following questions: (i) Do patients with periodontitis have impaired arterial stiffness compared to non‐periodontal diseased subjects? (ii) Is periodontal treatment effective as a means to improve arterial stiffness in patients with periodontitis? Literature Review Literature search was done on different databases up to September 2014. All clinical studies (excluding case reports) using PWV in patients with periodontitis were retrieved for a full‐text evaluation. A total of 10 studies were included. Patients with periodontitis have increased arterial stiffness compared to controls (PWV mean difference 0.85 m/s; 95% confidence interval: 0.53–1.16; p<0.00001). The only two interventional studies showed contradictory results on the effects of periodontal treatment on PWV. Conclusion Patients with periodontitis appear to have higher values of PWV compared to controls. The effect of periodontal treatment on arterial stiffness remains unclear.